Strength of Proof Letters Under Hand Legalized by Notaries - Fitriza Wirasari (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The duties and work of a notary as a public official are not limited to making authentic deeds but are also assigned to register and ratify documents under the hand there is legalization from authorized public officials. This study aims to determine the legalization process carried out by a notary, to find out about the responsibility of a notary to legalized underhand letters, to find out how far the power of proof of an underhand letter is as evidence in the trial process in court. This study uses a normative juridical research method. Normative juridical research is research conducted by reviewing applicable laws and regulations or applied to a particular legal problem. Based on the results of the study, it can be seen that the legalization practice carried out by a notary in this case the parties whose names are listed in the letter and affixed their signatures in the letter under the hand can no longer deny that the parties or one of the parties do not know the contents of the letter under the hand, because the contents have been read and explained first before the parties sign before a public official in this case is the notary concerned and in front of the witness. The responsibility of the notary towards the legalized letter under the hand is only limited to the certainty of the date and signature of the parties, that the undersigned in the letter under the hand, it is true that the parties themselves who are in the letter agreement under the hand are not other people. Because the notary must witness first hand and match the identity cards of the parties using the identity card on the day and date on which the letter was made. The legal consequences of proving in court with written evidence, in this case an underhand letter that has been legalized by a notary, have perfect evidentiary power if one of the parties does not deny the signature in the letter, therefore the underhand letter must meet the authenticity requirements determined by the Constitution. If the requirements determined by the law are met, then the legal force of proof becomes the judge's main consideration in making decisions relating to the subject matter being tried in court (Article 1881 paragraph (2) of the Civil Code).